PENGARUH EKSTRAK BERBAGAI BAGIAN TANAMAN MENGKUDU (Morinda citrifolia) TERHADAP PERKEMBANGAN PENYAKIT ANTRAKNOSA PADA TANAMAN CABE (Capsicum annuum L.) - Efri . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2010)
Effect of extraction from some parts of Mengkudu (Morinda citrifolia) to suppress anthracnose disease on chili (Capsicum annuum L). The research was conducted to study the effect of extract from some parts of Mengkudu on the growth of anthracnose disease on chilli (Capsicum annuum L). Some extraction of mengkudu parts such as from leaves, flowers and fruits and propineb fungicide were used in this research. Spore suspension of Colletotrichum capsici (108 spore/ml) used to inoculate chili plant one week before extraction of mengkudu (33 day after planting) was applicated. The result showed that application of leaf and flower extraction were effective to suppress disease incidence and severity, but fruit extraction was not effective. However, leaf and flower extraction did not significantly differ with propineb fungicide.